Prosedur tata kelola sebagai strategi partnership building - Heru Wibowo (Jurnal Good Governance, 2017)
Public policy management aims to produce good governance policies in modern society. However, with the diversity of public and governmental thinking it is necessary to find commonly agreed governance practices. Governance becomes a strategic aspect in building public trust to the government. It is this belief which, when grown in turn becomes a strategic supporting factor in building community-based partnerships, the success of building public trust will have an impact on the success of building partnerships, and vice versa. Governance is one of the strategies in partnership building that needs trust building support. This paper aims to find solutions to solving bureaucratic problems and political problems. For that will be analyzed supporting elements such as professionalism, paradigm implementation Civil Servants partner proportionally. The strategy includes fostering internal and external aspects that are relevant in realizing the partnership.Keywords: partnership, strategy, partnership building